Cutaneous manifestations of COVID-19 - Shaukat, Shehla; Butt, Ghazala; Hussain, Ijaz (Journal of Pakistan Association of Dermatologists, 2020)
The severe acute respiratory syndrome coronavirus 2 (SARSâ€CoVâ€2) and the disease it causes, termed coronavirus disease 2019 (COVIDâ€19), has rapidly swept across the world since its first known human manifestation on December 8, 2019. Confirmed cases are present in over 160 countries. Patients of COVID-19 infection present with diverse cutaneous manifestations seen in 0.2% to 20% of patients. This article summarizes different dermatological manifestations in patients with COVID-19 through literature review using Google Scholar, Sci Hub, PubMed and other online review articles. Case reports, case series and other studies which mentioned cutaneous manifestations in the patients with COVID-19 infection were added. The most common cutaneous manifestation of COVID-19 was found to be maculopapular (morbilliform) exanthem. Papulovesicular rash, urticaria, painful acral red purple papules (COVID toes), livedo reticularis and petechiae were other presentations. Majority of lesions were localized on the trunk; however, involvement of the hands and feet was also noted. Cutaneous involvement usually followed the respiratory symptoms; nonetheless, in a minority, it preceded systemic features. Majority of the studies failed to report any correlation between COVID-19 severity and skin lesions. Cutaneous manifestations may help in early diagnosis of disease and prompt treatment of COVID-19. Â 